Pengaruh Penerapan IFRS, Kualitas Auditor, Ukuran Perusahaan, Solvabilitas Terhadap Ketepatan Waktu Pelaporan Keuangan - Astri Fitria (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2021)
The study aims to examine empirically the influence of the implementation of IFRS, auditor quality, firms size and solvency to the timeless of the sub mission of financial statement of consumer goods companies wich are listed in the Indonesia Stock Exchange. The type of this study is the quantitative research. The population is consumer goods companies wich are listed in the Indonesia Stock Exchange and have submitted their 2015-2018 financial statements. The sampel collection technique by using saturated sampling and 36 consumer goods companies as samples. The data has been analyzed by using multiple linear regressions. The result of the study can be conclude that: (1) The implementation of IFRS give positive impact to the timeless of the sub mission of financial statement of consumer goods companies, (2) Auditor quality give positive impact to the timeless of the sub mission of financial statement of consumer goods companies, (3) Firms size give positive impact to the timeless of the sub mission of financial statement of consumer goods companies, (4) Solvency give positive impact to the timeless of the sub mission of financial statement of consumer goods companies.